Training - Denny, Richard; Lake, Nick; Turner, Barry; Gawith, Paul ([S.l.] : Man Management Ltd. [production company] ; Kuala Lumpur : First Training)
Discussed the role of trainer and trainees in attending every training. Explained how the manager organised, manage and handle a training programme to their employees.
Camera, Mark Lipscomb ; sound supervisor, Bill Cadman ; lighting director, Nigel Fisher
Keywords: Employees -- Training of; Training